2005
DOI: 10.1007/s00267-004-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Zone Problems and Environmental Strategies to be Implemented at Edremit Bay, Turkey

Abstract: This case study examines the coastal zone problems focusing on the existing conflicts between tourism and commercial activities on the coasts of Edremit Bay, Turkey, and attempts to suggest solutions to these problems. Edremit Bay is a characteristic example of such a conflict in collective use of natural resources. The study area, with its 100-km-long sandy beach, naturally attracts different coastal user groups with different beneficial expectations: in terms of rest and recreation for one group and commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…Alphan, Yilmaz (2005) reported that agriculture has increasingly grown over marginal areas and urban development occurred at the expense of prime croplands in the eastern Mediterranean coast of Turkey. Other parts of the Turkish Mediterranean coast such as Kusadasi and Edremit bay faced similar problems resulting from development (Kara et al 2013;Irtem et al 2005). Intense human uses also cause complex LU/LC changes around the Mediterranean basin (Salvati, Sabbi 2011).…”
Section: Quantifying From-to Changesmentioning
confidence: 99%
“…Alphan, Yilmaz (2005) reported that agriculture has increasingly grown over marginal areas and urban development occurred at the expense of prime croplands in the eastern Mediterranean coast of Turkey. Other parts of the Turkish Mediterranean coast such as Kusadasi and Edremit bay faced similar problems resulting from development (Kara et al 2013;Irtem et al 2005). Intense human uses also cause complex LU/LC changes around the Mediterranean basin (Salvati, Sabbi 2011).…”
Section: Quantifying From-to Changesmentioning
confidence: 99%
“…All the above degradation and destruction forms of the environment result in sometimes reversible but mostly irreversible conversions of land uses and land covers such as losses of forests, wetlands, and coastal and agricultural lands to urban areas (Davis and Froend 1999;Irtem et al 2005;Bolca et al 2007;Keleş et al 2008;Kesgin and Nurlu 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some areas intense agriculture for export relying on irrigation has expanded locally, taking advantage of favorable climate and/or European subsidies (see for example below or Valenzuela Montes & Mataran Ruiz, 2008;Suarez de Viveiro & Rodrigues Mateos, 2005;Irtem et al, 2005). For the Mediterranean coastlines of Spain, and Turkey and the Atlantic Southern coast of Portugal, the EEA confirms, almost without exception, the presence of salinated aquifers and declining quality of coastal (bathing) waters.…”
Section: Introductionmentioning
confidence: 77%
“…Suares de Vivero et al (2005) explicitly address the role of institutions and the lack of "adequate sectoral policies" in Spain. Irtem et al (2005) report similar problems and advocate institutional solutions for water resource and nature conservation problems emerging from urbanization and agricultural activities at Edremit Bay in Turkey.…”
Section: Introductionmentioning
confidence: 86%